The Remote Audit in Post-Pandemic Era: Professional Scepticism and Audit Quality Perspective - Acynthia Ayu Wilasittha (Journal of Economics, Business, and Government Challenges, 2022)
This study aims to determine the implementation of remote audit in the post-pandemic era by considering professional skepticism and the impact on audit quality that is applied during the remote audit. This research uses a descriptive qualitative method. The data source is primary data derived from interviews with auditors at KAP Kanaka Puradiredja, Suhartono (KAP KPS) in Surabaya who carried out remote audits during the Covid-19 pandemic. The results of the interview show the advantages and disadvantages of the implementation of remote audits during the Covid-19 pandemic and the role of professional skepticism and its effect on audit quality. Auditors feel that it is better to conduct an on-site audit compared to a remote audit in the post-Covid-19 era. However, there is a possibility that if technology can be utilized optimally by auditees and auditors, then a hybrid audit can be implemented to carry out audits that are more effective and efficient without compromising audit quality.